Effects of relative humidity, surface area and production route on hydrogen yields from water on the surface of plutonium dioxide - Webb, Kevin; Gregson, Colin; Holt, Josh; McLuckie, Bliss; Orr, Robin; Sims, Howard; Woodhead, David; Hobbs, Jeff; Steele, Helen; Currell, Fred; Jones, Luke; Pimblott, Simon; et al. (Frontiers in Nuclear Engineering, 2023)
Over 60 samples of plutonium dioxide (PuO2) powders of varying provenance have been exposed to humid atmospheres and the hydrogen generation rates measured by gas chromatography. The effects of relative humidity (RH), specific surface area (SSA), plutonium isotopics (absorbed dose), and overlying atmosphere have been investigated for ’as received’ PuO2 powders from the UK’s Thorp and Magnox reprocessing plants, high surface area powder produced in the laboratory and Magnox PuO2 that was re-calcined at 800, 900 or 950 °C. Hydrogen generation was shown to be susceptible to subtle influences with the most consistent results observed at 95% RH. However, it was shown that the measured (net) hydrogen decreases with decreasing RH and with atmosphere in the order: air>argon>nitrogen. There was no clear effect of SSA, apart from with the highest SSA samples (~40 m2.g-1) but these powders also have very different morphology, porosity and carbon content to the rest. The results presented substantially enhance the growing body of literature on the factors that determine hydrogen and gas generation from PuO2 that has significant implications for long term safe storage of plutonium globally.